Label‐Free Quantification Proteomics for the Identification of Mesenchymal Stromal Cell Matrisome Inside 3D Poly(Ethylene Glycol) Hydrogels. Issue 21 (27th September 2018) - Devaud, Yannick R.; Avilla‐Royo, Eva; Trachsel, Christian; Grossmann, Jonas; Martin, Ivan; Lutolf, Matthias P.; Ehrbar, Martin
Abstract: Cells modulate the functional properties of their environment by depositing extracellular matrix (ECM) proteins during biological processes in vivo and in vitro. Despite the ECMs central role in tissue formation, its quantification in hydrogels like Matrigel, which have a complex materials‐inherent biopolymer composition is exceptionally challenging. Here, the use of protein‐free, synthetic poly(ethylene glycol) hydrogels enables the analysis of deposited human bone marrow mesenchymal stromal cells ECM directly harvested from fresh 3D cell cultures by a tandem mass spectrometry (LC‐MS/MS) method. In this study, it is proved that a label‐free LC‐MS/MS quantification method can selectively identify proteins deposited in 3D synthetic hydrogels following different growth factor (GF) treatments. Furthermore, it is shown that the sequence in which GFs are administered and the choice of stimuli significantly influences the number and abundance of ECM proteins. Therefore, this provides a versatile method to optimize GF treatments in synthetic hydrogel‐based regenerative medicine and tissue engineering approaches. Abstract : Cell‐secreted extracellular matrix (ECM) components modulate the initial cell–biomaterial interface. This paper describes a label‐free tandem mass spectrometry‐based method to identify cell‐deposited ECM components in synthetic hydrogels. This method is employed to evaluate ECM compositions in 3D cultures of human bone marrow mesenchymal stromal cells.